Public Debt Transparency in Uganda : A Stock-Taking of Public Debt Data Transparency, and Disclosure of Debt Management and Domestic Borrowing Practices - Stucka, Tishomir (World Bank, Washington, DC, 2021)
With public debt levels rising in Uganda, debt transparency is critical for providing accountability to the general public, enabling informed decisions by domestic businesses, and allowing foreign creditors to understand borrowing trends. Debt and debt management transparency improve accountability and, potentially, borrowing outcomes. Over the past decade, the emergence of new external creditors in Uganda has opened new sources of financing and has in parallel increased the complexity of public debt portfolios. This makes debt and debt management transparency even more important. While new sources of funding can provide opportunities to advance development goals, they can also lead to significant economic costs, if debt is not managed well. Uganda is doing well in terms of public debt and debt management transparency compared to other Sub-Saharan, IDA-eligible countries, when assessed through the lens of the World Bank’s (WB) Public Debt Heat Maps. These Heat Maps present an assessment based on the availability, completeness and timeliness of public debt statistics and debt management documents posted on national authorities’ websites. The continuous efforts in publishing debt data in Uganda have resulted in good data disclosures of explicit and implicit public debt data when compared to peers. That said, the transparency stock-taking is not designed to make statements about the accuracy of the data or the quality of the analyses (the in-house debt management strategy and debt sustainability analysis) nor does it make statements about institutional shortcomings and legal weaknesses that would need to be addressed to arrive at sound, transparent borrowing processes. Despite the good outcomes of the transparency assessment based on the WB Heat Map methodology, the report singles out a few dimensions that require further attention such as: i. reducing time lags by publishing domestic arrears data semiannually, ii. providing more granularity on state-owned enterprise debt by listing the largest ten with the corresponding debt breakdown, iii. including a section on collateralized debt in the Annual Debt Report and minimizing confidentiality clauses; and iv. where permissible publishing entire or parts of contracts to further enhance transparency.